Entrepreneurship and Green Finance Practices : Avenues for Sustainable Business Start-ups in Asia - Syed Ali, Raza (Emerald Publishing Limited, 2024)
Entrepreneurship and Green Finance Practices focuses on critical issues such as the role of Green Financing in Green Entrepreneurship in Asian Countries and looks for the mechanisms that can help in idea-generation and the launching of successful Green Start-ups.